Thinkers of the Muslim East on Commercial Ethics - Azizkulov Akram Abduraxmonovich (Peerian Journals Publishing, 2022)
This article describes the rules of etiquette, which were presented by Eastern thinkers in particular Husayn Kashifi and Gazali for representatives of trade. The article also notes that the commercial etiquette that was presented by the thinkers has not lost its relevance today.
Keywords: Husayn Kashifi; Gazali; social relations; professional ethics